CORRELATION BETWEEN STUDENTS’ THINKING STYLE AND ACADEMIC ACHIEVEMENT - Febri Diyas Romadhani; Deanita Noviany Lukmana (PROJECT (Professional Journal of English Education), 2018)
This study aimed to consider the relationship between students’ thinking style and academic achievement. The researcher used correlational method. The population of this study was students at Madrasah Aliyah Negeri Cimahi. There were 30 students chosen as the sample. In collecting the data, this study used questionnaire that was developed from Sternberg’s theory. In this theory, there were two forms of thinking style, which were global and local. Regarding the result, this study found that there was significant correlation between students’ thinking style and their academic achievement. The level of significance was 0.00. This means that students’ thinking style affected their achievement in school.